Summary report of a digestibility trial on Atlantic salmon in seawater - Koppe, Wolfgang; Lamborelle, Georges (Zenodo, 2021)
This report represents the results of an experiment performed by Matís ohf for Mowi ASA, represented by Riesen Guido and Laura Martinez Rubio. The trial objective was to test 35 different feed raw materials in triplicates on digestibility of crude protein and amino acid in Atlantic salmon ( Salmo salar ). The test diets were formulated and supplied by Mowi and produced by DTI or Nofima. Each test diet contained 30 % of the test raw material. The trial was carried out at Matís Aquaculture Research Station (MARS) in a RAS with 24*600 litre tanks. The feeding trial contained five rounds with 2 to 3 weeks of feeding per round. The average temperature was 12.6 °C and salinity was 33.3 ppt. The faeces samples were collected by stripping and immediately stored after sampling at – 24°C until they got freeze dried. The analytical part was done at LUFA Nord-West. Uneaten feed was collected daily to calculate the feed intake. Funding: MOWI Feed